中国国有工业国际竞争力初探 = International competitiveness of China's state-owned industries - 杨海斌 Yang, Haibin (2010)
随着开放的世界经济和全球化过程中，“地方经济“的界限“全球经济“正在被打破了，并在不同的国家在国际市场的竞争正在变得日益严重。国际竞争力的研究因此成为一个全球性质的热门话题。作为世界经济的总体布局基本上还处于阶段工业化，在各行业的竞争最根本的还是形式方面的国际竞争。中国的国有工业，这是国民经济的支柱，在振兴经济发挥关键作用，参与国际竞争。因此，具有重要意义，使在研究的背景下对中国国有工业的竞争力世界经济。 With the opening up of the world economy and the process of globalization, the boundaries of "local economy" and "global economy" are being broken up, and competition among different countries in international markets is becoming increasingly severe. The study of international competitiveness has therefore become a hot topic of worldwide nature. As the general layout of the world economy is basically still in the stage of industrialization, competition in various industries still forms the most fundamental aspect of international competition. China's state-owned industries, which are the backbone of the national economy, play a crucial role in revitalizing the economy and participating in international competition. It is therefore of great significance to make a study on the competitiveness of China's state-owned industries in context of the world economy.